KAJIAN SISTEM DRAINASE MELALUI SUMUR RESAPAN DI KAWASAN PERUMAHAN WILIS INDAH 2 KOTA KEDIRI - Muhammad Dicky Arwidyanto; I Wayan Mundra; Sriliani Surbakti (SONDIR, 2022)
The Wilis Indah 2 Residential Area is located in the Pojok Village, Mojoroto District, Kediri City, East Java and is one of the most crowded and dense residential areas in the city center. With an area of ​​± 170,000 m2, the drainage channel in this residential area often inundates, especially during the rainy season for a long time due to the high intensity of rain and the drainage system that cannot accommodate the excess flow of water that comes. So from these conditions it is necessary to study to overcome the existing flood problems. The method used for this research is data collection which will be analyzed from various sources. Maximum design rainfall analysis was carried out with a comparison of the two methods and the results of the analysis from the Log Pearson Type III method were used. In the intensity analysis, a 5-year rainfall return period was used with the result of 118,730 mm. In the existing channel, an analysis of the channel capacity was also carried out. After that, an evaluation of the planned flood discharge with channel capacity was carried out, as many as 12 channels did not meet. One of the alternatives given is the design of infiltration wells with a circular cross section with a diameter of 1.2 meters and a depth of 2 meters. Based on research, the existing condition of the drainage system in the Wilis Indah 2 Housing area is not in good condition. Solutions for handling channel problems are adjusted to the conditions of each channel and several channels are given alternative infiltration well planning with the aim of conserving water resources where rainwater is infiltrated into the ground before entering the canal.